2014
DOI: 10.3892/or.2014.3690
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial changes in endometrial carcinoma: Possible role in tumor diagnosis and prognosis (Review)

Abstract: Endometrial carcinoma (EC) is a solid neoplasia for which a role for mitochondria in cancer progression is currently emerging and yet represents a diagnostic and prognostic challenge. EC is one of the most frequently occurring gynecological malignancies in the Western world whose incidence has increased significantly during the last decades. Here, we review the literature data on mitochondrial changes reported in EC, namely, mitochondrial DNA (mtDNA) mutations, increase in mitochondrial biogenesis and discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…Interestingly, our findings show a unique phenotypic difference between syngeneic tumors growing in Sparc -deficient mice; that is, the significant increase in mitochondrial number may reflect increased mitochondrial biogenesis concomitant with the upregulation of bioenergetic metabolic pathways. This is in accord with earlier studies that reported increased mitochondrial replication with changes in shape, size and number to influence metabolic remodeling of a myriad of physiological and pathological conditions including cancer [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, our findings show a unique phenotypic difference between syngeneic tumors growing in Sparc -deficient mice; that is, the significant increase in mitochondrial number may reflect increased mitochondrial biogenesis concomitant with the upregulation of bioenergetic metabolic pathways. This is in accord with earlier studies that reported increased mitochondrial replication with changes in shape, size and number to influence metabolic remodeling of a myriad of physiological and pathological conditions including cancer [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Mutations, deletions, and changes in mtDNA copy number have been observed in cancers, particularly in response to therapy ( 36 38 ). However, the mechanisms and the clinical relevance of these phenomena remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian, cervical and endometrial cancers are common gynecological malignancies, whose incidence are increasing (24)(25)(26). This is particularly evident in the case of ovarian cancer, which poses a serious threat to female health (25).…”
Section: Discussionmentioning
confidence: 99%